2017
DOI: 10.1016/j.amjcard.2017.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Placebo-Controlled Randomized Controlled Trials on the Prevalence of Statin Intolerance

Abstract: The prevalence of intolerance varies widely. Stopping statin therapy is associated with worse outcomes in patients with cardiovascular disease. Despite extensive studies, the benefits and risks of statins continue to be debated by clinicians and the lay public. We searched the PubMed, Medline, and Cochrane Central Register of Controlled Trials (CENTRAL) databases for all randomized controlled trials of statins compared with placebo. Studies were included if they had ≥1,000 participants, had patients who were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…The authors of the meta‐analysis raised the possibility of the ‘nocebo effect’ being responsible for the high rate of reporting of muscle symptoms in non‐blinded trials . These findings were confirmed in a more recent meta‐analysis …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors of the meta‐analysis raised the possibility of the ‘nocebo effect’ being responsible for the high rate of reporting of muscle symptoms in non‐blinded trials . These findings were confirmed in a more recent meta‐analysis …”
Section: Introductionmentioning
confidence: 80%
“…22 These findings were confirmed in a more recent meta-analysis. 23 Evidence relating to the role of the nocebo effect in statin intolerance was recently extensively reviewed by Tobert and Newman. 2 Since then, Gupta et al, in a retrospective analysis of the Anglo-Scandinavian Cardiac Outcomes Trial, found no difference between the incidence of muscle symptoms in patients taking atorvastatin 10 mg compared with placebo [hazard ratio 1.03, 95% confidence interval (CI) 0.88-1.21] in the initial double-blind phase of the trial, whereas in a later-open-label extension, significantly more muscle symptoms were reported in the statin-treated group 1.41 (1.10-1.79).…”
Section: Introductionmentioning
confidence: 99%
“…The tolerability of statins has been evaluated in numerous trials in different patient populations 12 14 46. Possible side effects are rare or very rare, and include abdominal pain, mild hepatitis, pancreatitis, anaemia, myopathies or peripheral neuropathies or allergic reactions.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…Possible side effects are rare or very rare, and include abdominal pain, mild hepatitis, pancreatitis, anaemia, myopathies or peripheral neuropathies or allergic reactions. Meta-analyses have found that statins are equally safe as control treatment regarding adverse and serious adverse events, and that rates of discontinuation and the most frequent side effect myopathy were equal between simvastatin and placebo in clinical trials 14 46. Safety of statins in chronic liver disease has been assessed in only a few clinical trials, but reviews of observational studies report high safety and low risk of adverse events 10 47 48…”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…Im Gegensatz dazu liegt die Inzidenz von Muskelbeschwerden unter Statintherapie in randomisierten Studien nur bei 3-5 % [9,10] und damit im Bereich des Placeboarms. Zudem zeigt eine kürzlich publizierte Metaanalyse von 22 Studien auch keinen signifikanten Unterschied zu Placebo bezüglich Therapieabbruch und Auftreten von Myopathie [11]. Interessanterweise entsprach das mittlere Erkrankungsalter in der Subgruppe der HMGCR-positiven Patienten ohne Statinexposition mit ca.…”
Section: Statinassoziierte Muskelbeschwerden (Sams)unclassified